2013
DOI: 10.1002/hipo.22195
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and stimulus-type tuning in the LEC, MEC, POR, PrC, CA1, and CA3 during spontaneous item recognition memory

Abstract: According to the "two streams" hypothesis, the lateral entorhinal (LEC) and the perirhinal (PrC) cortices process information related to items (a "what" stream), the postrhinal (POR) and the medial entorhinal cortices (MEC) process spatial information (a "where" stream), and both types of information are integrated in the hippocampus (HIP). However, within the framework of memory function, only the HIP is reliably shown to preferentially process spatial information, and the PrC items' features. In contrast, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 77 publications
(113 reference statements)
4
31
0
Order By: Relevance
“…In the three areas, representations of identical events are most closely associated (correlation of odd/even trials). Thus, although PRC, LEC and MEC exhibit similarity in mixed selectivity at the single neuron level, RSA reveals that information is organized in distinct but complementary ways (see also Ahn and Lee, 2015; Beer et al, 2013; Deshmukh and Knierim, 2011; Ohyama et al, 2012). …”
Section: The Hippocampus Mec Lec Ofc and Perirhinal Cortex Create mentioning
confidence: 99%
“…In the three areas, representations of identical events are most closely associated (correlation of odd/even trials). Thus, although PRC, LEC and MEC exhibit similarity in mixed selectivity at the single neuron level, RSA reveals that information is organized in distinct but complementary ways (see also Ahn and Lee, 2015; Beer et al, 2013; Deshmukh and Knierim, 2011; Ohyama et al, 2012). …”
Section: The Hippocampus Mec Lec Ofc and Perirhinal Cortex Create mentioning
confidence: 99%
“…These include grid cells, head direction cells, border/boundary vector cells and speed cells (Hafting et al, 2005; Barry et al, 2006; Savelli et al, 2008; Solstad et al, 2008; Lever et al, 2009; Kropff et al, 2015). There is now growing support from lesion and single unit recording studies for the suggestion that LEC is involved in processing past and present locations of objects (Deshmukh and Knierim, 2011; Beer et al, 2013; Hunsaker et al, 2013; Tsao et al, 2013; Van Cauter et al, 2013; Wilson et al, 2013a,b; Chao et al, 2016; Keene et al, 2016). Our own work has shown that LEC is needed to associate together features of a local environment including spatial locations of objects (Wilson et al, 2013a,b).…”
Section: Introductionmentioning
confidence: 99%
“…While long-term recognition memory formation has been shown to require expression of immediate early genes and a number of transcription factors (Zhu et al, 1995, Bozon et al, 2003, Warburton et al, 2005, SoulĂ© et al, 2008, McNulty et al, 2012, Seoane et al, 2012, Barbosa et al, 2013, Beer et al, 2013), little is known about how these genes are regulated. Epigenetic regulation processes have been shown to be important for long term memory.…”
Section: Introductionmentioning
confidence: 99%